Ṭaşköprüzāde Ahmed Efendi’s Commentary on the Ethical Philosophy of ʿAḍud al-Dīn al-Ījī: Theory and Praxis of Muslim Philosophical Ethics in the Sixteenth Century = šrḥ ṭāškbrī zādh āʾḥmd āʾfndī ʿlā ālflsfa ālāʾḫlāqīa lʿḍd āldīn ālāʾīǧī: ālāʾḫlāq ālflsfīa ālāʾslāmīa tnẓīrā ūtṭbīqā fī ālqrn ālʿāšr ālhǧrī/ālsāds ʿšr ālmīlādī - Salem, Feryal (Journal of Islamic ethics, 2022)
The ethical treatise of ʿAḍud al-Dīn al-Ījī (d. 756/1355), al-Akhlāq al-ʿAḍudiyya, is a key work in the genre of Muslim philosophical ethics whose primary significance includes the numerous lengthy commentaries extant until today, which depict the ethical discourse over a long period of time from a wide range of Muslim settings. As a prominent Ashʿarī and Shāfiʿī scholar of the Īlkhānid era, al-Ījī’s work played an important role in the continuation of the intellectual genealogy of writers on ethical philosophy, that includes Ibn Sīnā (Avicenna, d. 428/1037), Miskawayh (d. 421/1030), al-Ghazālī (d. 505/1111), and al-Ṭūsī (d. 672/1274). As al-Ījī’s ethics became prevalent within the realm of Ottoman scholarship, the impact of this treatise moved beyond Central Asia and Iran and into the Ottoman scholastic networks, where the commentaries on al-Akhlāq al-ʿAḍudiyya were studied. This article demonstrates facets of ethical philosophy during the tenth/sixteenth century by examining the commentary of a prominent Ottoman scholar of this era, namely Ṭaşköprüzāde (d. 968/1561), on al-Ījī’s treatise on ethics.